Karstology : Karsts, caves and springs : Elements of Fundamental and applied Karstology - Gilli, Éric (CRC Press, 2014)
Karst landscapes are home to 25 percent of the world's drinking water supplies, and in many countries water supply is highly dependent on karst aquifers. Their unique structures, containing many voids, are a particular problem for building corporations and land developers. This book, written by the well-known karstologist Eric Gilli, presents a diverse range of chapters on history of karstology, aquifers and their characterization, water supply management, coastal and submarine karsts, evolution of karst and paleokarst, paleontology, tourism, and oil and mineral reserves.